Predictors of Conversion to Multiple Sclerosis in Patients with Clinical Isolated Syndrome Using the 2010 Revised McDonald Criteria. (1st November 2012) - Alroughani, R.; Al Hashel, J.; Lamdhade, S.; Ahmed, S. F.
Abstract : Background . Clinically isolated syndrome (CIS) is the first neurologic episode of multiple sclerosis (MS). Magnetic resonance imaging (MRI) and clinical features are used to predict risk of conversion to MS. Objectives . The aim of this prospective study is to evaluate predictors of conversion of CIS to McDonald MS. Method . 97 patients with CIS have been followed for 2 years. Age of onset, gender, initial clinical presentation, and MRI brain and spine were assessed. The 2010 revised McDonald criteria were applied. Results . Fifty-nine patients (60.8%) with CIS converted to McDonald MS after 10.1 + 4.2 months. Thirty-seven (38.1%) of the convertors satisfied the diagnostic criteria based on the radiological parameters, while 21.7% sustained their second clinical events. A multivariate regression analysis revealed that high number of lesions in MRI (P = 0.001 ) and earlier age of onset (P = 0.043 ) predicted the conversion of CIS to McDonald MS. Gender (P = 0.5 ) and initial clinical presentation (optic pathway (P = 0.4 ), supratentorial (P = 0.91 ), brain stem/ cerebellum (P = 0.97 ), and spinal (P = 0.76 )) were not statistically significant. Conclusion . Age of onset and MRI parameters can be used as predictors of CIS conversion to McDonald MS. Application of the 2010 revised McDonald criteria allows an earlier MS diagnosis.